2022
DOI: 10.1039/d2qo01003h
|View full text |Cite
|
Sign up to set email alerts
|

Neutrally photoinduced MgCl2-catalyzed alkenylation and imidoylation of alkanes

Abstract: We report a practical protocol for oxidation of the chloride ion (Cl-) to chlorine radical (Cl.) via a photoinduced MgCl2 catalysis, avoiding the use of strong acid, formal oxidant, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…We start our investigation with the reaction of 2 mmol of repeat units of isotactic polypropylene (iPP) 1 a and 10 mol% of methyl acrylate (MA) 2 a in presence of TBA(FeCl 4 ) [13b] in chlorobenzene under 390 nm LEDs irradiation at 120 °C for 2 h. The desired functionalized polypropylene (iPP-MA) was successfully ob-tained with 1.1 % of level of functionalization (LOF) (Figure 1). The presence of the functional groups could be well confirmed by 1 H NMR (nuclear magnetic resonance), 13 C NMR, heteronuclear multiple bond correlation (HMBC) spectra in CDCl 3 . Interestingly, the incorporation of such a small amount of the polar groups would significantly enhance the transparencies, mechanical property and change the thermal property.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…We start our investigation with the reaction of 2 mmol of repeat units of isotactic polypropylene (iPP) 1 a and 10 mol% of methyl acrylate (MA) 2 a in presence of TBA(FeCl 4 ) [13b] in chlorobenzene under 390 nm LEDs irradiation at 120 °C for 2 h. The desired functionalized polypropylene (iPP-MA) was successfully ob-tained with 1.1 % of level of functionalization (LOF) (Figure 1). The presence of the functional groups could be well confirmed by 1 H NMR (nuclear magnetic resonance), 13 C NMR, heteronuclear multiple bond correlation (HMBC) spectra in CDCl 3 . Interestingly, the incorporation of such a small amount of the polar groups would significantly enhance the transparencies, mechanical property and change the thermal property.…”
Section: Resultsmentioning
confidence: 79%
“…A possible mechanism was proposed as shown in Figure 3 base on previous work [13] . Under the irradiation of LEDs, the excited state of TBAFeCl 4 would generate the Cl-radical and Fe (II) via LMCT.…”
Section: Resultsmentioning
confidence: 99%
“…We then tried to add other iron salt catalysts instead of FeCl 3 , such as FeCl 2 and Fe­(OAc) 2 , and the reactions could proceed smoothly, but showed lower catalytic activities and afforded the products 3a in 85% and 87% yields, respectively, which indicated that iron was essential to the reaction (Table entries 3 and 4). Replacing FeCl 3 with CuCl 2 , , CeCl 3 , or MgCl 2 , which are known to produce chlorine radicals upon irradiation, were observed to be significantly less effective (Table entries 5–7). Control experiments revealed that no product was observed without HCl (Table entry 8), and only trace amounts of product 3a were obtained when H 2 SO 4 was used instead of HCl (Table entry 9).…”
Section: Resultsmentioning
confidence: 99%
“…). Replacing FeCl 3 with CuCl 2 , 59,60 CeCl 3 ,61 or MgCl 2 ,62 which are known to produce Optimization of the Reaction Conditions a…”
mentioning
confidence: 99%
“…8c In addition, the epoxide 67 could be obtained by treating compound 30 with m-chloroperoxybenzoic acid. 17 Compound 68 with a remote hydroxy group was produced by LiAlH 4 reduction, and compound 31 with a free OH group could further undergo nucleophilic substitution or condensation reactions to yield compounds 69−71, in which terminal alkynes and bioactive moieties were introduced efficiently. Moreover, deprotection of product 39 might quantitatively produce compound 72, which could be used to prepare heterocyclic compounds 73−74.…”
mentioning
confidence: 99%